Pengaruh Website Cinema 21 Terhadap Loyalitas Pengunjung (Studi Kasus Cinema 21 Kota Batam) - Rika Harman (Universitas Putera Batam, 2015)
Websites began to be known in Indonesia around 1998, in which only large companies can afford to have it. At that time, the website is a technology that is quite expensive to own. So many entrepreneurs and manufacturers discourage them to be able to have this media campaign. The steps of making a web services provider that offers low prices make these companies desire to have a cheap website just be a dream. That was then, now there are virtually billions of web pages that enliven the virtual world. Most of these are commercial web site that is business and commerce. Apparently the media campaign in the form of a website is very important in the business world. The proof lately many large and small businesses have used the website as a medium of promotion in marketing products or services. Websites that not only functions as a promotional tool but also as an effort to increase the prestige (prestige) of a company has made ​​a lot of bold entrepreneurs to pay high enough to have this online media. Often we ask questions when we attended seminars that discuss about the website,